2016
DOI: 10.1001/jamaoto.2016.0927
|View full text |Cite
|
Sign up to set email alerts
|

Mucous Cytokine Levels in Chronic Rhinosinusitis–Associated Olfactory Loss

Abstract: IMPORTANCE Olfactory loss is a frequent symptom of patients with chronic rhinosinusitis (CRS), but our understanding of how inflammatory cytokines affect olfaction is limited. OBJECTIVES To examine whether inflammatory cytokines are present in the olfactory cleft and whether they correlate with objective olfaction. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional study, patients with CRS underwent quantitative olfactory testing using the Sniffin Sticks test to calculate a composite threshold discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 23 publications
(28 reference statements)
6
84
2
Order By: Relevance
“…We did, however, find that IL‐6 levels were associated with significantly lower SIT scores. This result is in contrast to that by Schlosser et al, which conversely demonstrated a weak positive correlation between mucus IL‐6 levels and olfactory identification scores . Of note, both IL‐6 and IL‐6 receptor expression have been reported in olfactory mucosa, and elevations in IL‐6 have been associated with reduced neurogenesis …”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…We did, however, find that IL‐6 levels were associated with significantly lower SIT scores. This result is in contrast to that by Schlosser et al, which conversely demonstrated a weak positive correlation between mucus IL‐6 levels and olfactory identification scores . Of note, both IL‐6 and IL‐6 receptor expression have been reported in olfactory mucosa, and elevations in IL‐6 have been associated with reduced neurogenesis …”
Section: Discussioncontrasting
confidence: 96%
“…We did, however, find that the Th2‐associated cytokines IL‐5 and IL‐13 are secreted in high levels within olfactory cleft mucus of patients with CRSwNP. Interestingly, Schlosser et al recently reported that mucus IL‐5 levels were inversely correlated with objective olfactory function in all patients with CRS . We identified this association as well, while noting similar findings for the Th2‐associated cytokine IL‐13, though in our case these associations seemed to be driven primarily by the CRSwNP phenotype.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Despite apparent pathophysiological relevance 32-35 , our study found that IL-4 was a poor biomarker for Th2-high CRS, largely because mucus levels were indistinguishable from healthy controls. This is in line with recent studies that have also shown small or no differences in IL-4 levels between individual CRS phenotypes or compared to healthy controls 36-39 , but is in contrast to some prior studies that did confirm elevated levels of IL-4 in CRS compared to controls 40-42 . We suspect that much of these conflicting results may be attributable to differences between assays and variability in approaches for mucus collection and processing.…”
Section: Discussionsupporting
confidence: 91%
“…This technique would collect mucus from the OC, although it would not allow one to determine whether it was produced by olfactory mucosa or respiratory mucosa. In a small, single‐institution pilot study, we were able to detect inflammatory proteins in mucus collected from the olfactory cleft and show that some correlate with objective olfactory function . The goal of the current study was to confirm and expand on these findings, utilizing a cohort recruited from several centers across North America.…”
mentioning
confidence: 77%